Multi-authority attribute-based encryption with efficient revocation - Kai ZHANG; Jian-feng MA; Hui LI; Jun-wei ZHANG; Tao ZHANG (Tongxin xuebao)
Multi-authority attribute-based encryption was very suitable for data access control in a cloud storage environment.However,efficient user revocation in multi-authority attribute-based encryption remains a challenging problem that prevents it from practical applications.A multi-authority ciphertext-policy attribute-based encryption scheme with efficient revocation was proposed in prime order bilinear groups,and was further proved statically secure and revocable in the random oracle model.Extensive efficiency analysis results indicate that the proposed scheme significantly reduce the computation cost for the users.In addition,the proposed scheme supports large universe and any monotone access structures,which makes it more flexible for practical applications.